2017
DOI: 10.1016/j.bpj.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Framework for Quantifying Bacterial Tolerance

Abstract: Antibiotic tolerance and persistence are often associated with treatment failure and relapse, yet are poorly characterized. In distinction from resistance, which is measured using the minimum inhibitory concentration metric, tolerance and persistence values are not currently evaluated in the clinical setting, and so are overlooked when a course of treatment is prescribed. In this article, we introduce a metric and an automated experimental framework for measuring tolerance and persistence. The tolerance metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
129
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 30 publications
2
129
4
1
Order By: Relevance
“…One reason for this is that, by definition, tolerant cells survive but do not grow in the presence of antibiotics (23, 36, 37), making it difficult to select tolerant bacteria. While many attempts have been made to develop methods to select tolerant cells in a heterogeneous population (11,(19)(20)(21), none of these can be used to routinely quantify the tolerance of a bacterial isolate in the clinic. Very recently, a method, called TDtest, which can easily detect antibiotic tolerance using a modified disk diffusion assay was described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this is that, by definition, tolerant cells survive but do not grow in the presence of antibiotics (23, 36, 37), making it difficult to select tolerant bacteria. While many attempts have been made to develop methods to select tolerant cells in a heterogeneous population (11,(19)(20)(21), none of these can be used to routinely quantify the tolerance of a bacterial isolate in the clinic. Very recently, a method, called TDtest, which can easily detect antibiotic tolerance using a modified disk diffusion assay was described.…”
Section: Discussionmentioning
confidence: 99%
“…Such a method will subsequently enable the design of drugs to eradicate persistent infections. Several attempts have been made to solve the mysteries of antibiotic tolerance, particularly by isolating and quantifying tolerant variants from a heterogeneous population, yet none have been simple or cost-effective enough for use in clinics on a routine basis (11,(19)(20)(21).…”
mentioning
confidence: 99%
“…In this study, we observed a novel form of antibiotic tolerance. Tolerance has been defined as increased time to killing 26 , as opposed to resistance (a change in the MIC), or persistence (the ability of a subpopulation of clonal bacteria to survive high concentrations of antibiotic 5 ). Tolerance to beta lactams such as ampicillin has been observed in E. coli cultures that exhibit slow growth or a long lag phase 5 , and E. coli mutants with longer lag phases can be selected through experimental evolution to match the time of treatment 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…High mortality rates and increasing health 3 care costs associated with fighting the bacterial infections call for designing new 4 effective therapeutic strategies [7,26]. A major challenge in overcoming treatment 5 failures is coming from ineffective eradication of antibiotic-susceptible 6 bacteria [12,29,34]. Despite the introduction and wide application of a very large range 7 of antibiotics since the 1940s, important aspects of how antibiotics clear bacterial 8 population at all levels (molecular, cellular and population) remain not well clarified.…”
mentioning
confidence: 99%
“…Even at concentrations above MIC, some bacteria survive a short-term exposure to 319 antibiotics before being affected by it. This ability of bacterial population is known as 320 tolerance [6]. In contrast to resistance, which is quantified by the MIC, tolerance is 321 poorly characterized.…”
mentioning
confidence: 99%